The Effect of Context-Based Problem-Solving Instructional Approach on Gender Differences in Affective Characteristics and Mechanics Achievement of Pre-Service Science Teachers - Peşman, Haki; Arı, Üzeyir (My University, 2023)
This study investigated the effect of the context-based problem-solving instructional approach on the difference between female and male science teacher candidates in the attitudes and motivations toward physics and achievement in mechanics. 27 (9 males and 18 females) senior pre-service science teachers studying at the Science Teacher Education program at Fırat University participated in the study. The study was designed as a one-group pre-test and post-test design. In the study, the Affective Characteristics Questionnaire (ACQ), used for assessing attitude and motivation towards physics, and the Mechanics Achievement Test (MAT), used for assessing achievement in mechanics and developed by the researchers, were both used as pre-tests and post-tests as instruments. In addition, nine context-based questions were developed by the researchers in order to carry out the context-based problem-solving instructional approach as the experimental intervention. As a result, although no statistically significant improvement was observed in the preservice science teachers’ attitudes and motivations towards physics, it was observed that there was statistically and practically significant progress in the mechanical achievement test scores. In the analysis based on the interaction of males’ and females’ progress in mechanics achievement, statistically significant interaction could not be observed due to the limitation of the sample size. However, female preservice science teachers were observed to benefit more than the males from the intervention with a small-medium effect size. That is to say, a practically significant interaction was observed. Therefore, the context-based problem-solving instructional approach seems to minimize the gender gap in mechanics or physics achievement potentially.
Keywords: Context-Based Problems; Problem-Solving Instructional Approach; Pre-Service Science Teachers